PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS KARAKTER PADA PEMBELAJARAN QUANTUM POKOK BAHASAN PERSAMAAN GARIS LURUS SMP KELAS VIII - Dwi, Wicha; Dafik, D; Susanto, S (Kadikma, 2012)
Abstract. Quantum Teaching is a concept that describes the new ways to facilitate the learning process. This concept has been widely used in a class to improve the student achievement. Type of this research is a developmental research by using 4-D model, it consists 4 steps namely define, design, develop, and disseminate. The subject of a research is an equation of straight line for grade VIII A of SMP Negeri 1 Maesan. The data collection methods used in this research are validation, observation, questionnaire, and test. The result of the research are Sillaby, Teaching Plan, Teacher Book, Student Book, Work Sheet, and achievement test. All the learning materials obtained from this research satisfy the effectiveness criteria and the student achievement is 85.18% of student get score bigger than 60. Key Words : Developmental Research, Characters, Quantum Teaching, 4-D model.